Edukasi Kesehatan Mental Melalui Media Digital Sebagai Upaya Menghapus Stigma Gangguan Mental - Fitria Maudy Wardhani (Jurnal Pendidikan dan Penciptaan Seni, 2023)
Mental health stigma is closely related to the assumption that mentally ill people have a bad view in the eyes of society. Stigma in mental health disorders needs to be reduced through mental health promotion actions. Just like physical illness, mental health disorders can also lead to serious conditions if not taken care of. therefore the creator wants to use social media as education about mental health to the public so that they can increase knowledge about how stigma is circulating in the community. In the creation of this media work using the creative process method. Problem solving is based on data and facts related to mental health problems as stigma. The results of the data are packaged into social media content as a means of education about mental health. This conflict is represented by the composition of digital illustrations and information that as a whole form a single unit which when opened on social media, the audience can slide it to get more information about myths and facts about mental health.